The Influence of Workload, Knowledge, Motivation on Medical Record Quality Through Doctor Compliance - Arrandhikasari, Devina; Pamungkas, Rian Adi; Saptaningsih, Agusdini Banun (International Journal of Nursing and Health Services (IJNHS), 2023)
Background. Medical records are records and documents containing the patient's identity, examination, treatment, actions and other services that have been provided to patients. Medical records are said to be of high quality if the data and information are complete and can be read by those entitled to it from time to time as a continuous communication tool. Objective: The study aimed to analyze the effect of workload, knowledge and motivation through doctor compliance that can improve the medical record quality. Method: This study uses a quantitative approach with a causal design research using SPSS-Path Analysis. Result: There was no effect of workload on the quality of medical records through doctor's compliance, there was an influence of knowledge on the quality of medical records through doctor's compliance and there was an influence of motivation on the quality of medical records through doctor's compliance. Implication: This study proves that the amount of doctor's compliance is able to mediate the effect of knowledge and motivation which can improve the quality of medical records. Hospital management is expected to be able to motivate doctors to understand changes in the current digitalization era and to improve the level of awareness of doctors to work in an orderly administration. Keywords: Compliance, Knowledge, Medical Record Quality, Motivation, Workload